Student Experience And Digital Engagement As Drivers Of Private Higher Education Reputation: A Systematic Literature Review 2005–2025 - Petiana Indriati; Sri Widyastuti; Zulkifli Zulkifli (Publikasi Indonesia, 2025)
Fierce competition among private universities demands that institutions cultivate reputations rooted in student experience and a robust digital presence. Empirical evidence on the interplay between student experience, digital engagement, e-service quality, electronic word-of-mouth (e-WOM), brand image, and institutional reputation remains fragmented and often contradictory. This study synthesises the 2005–2025 literature through a Systematic Literature Review guided by PRISMA 2020. Searches in Scopus, Web of Science, ProQuest, Google Scholar, and Garuda yielded 125 records; after deduplication, screening, and JBI appraisal, ten mixed-methods studies (quality score ? 70 %) were analysed. Thematic synthesis reveals three dominant patterns: (1) student experience—especially academic interaction and support services—consistently enhances brand image and reputation; (2) rich digital interactivity sparks positive e-WOM that strengthens institutional perceptions; and (3) e-service quality shapes reputation indirectly via student satisfaction. The research landscape is limited by a predominance of cross-sectional designs and a scarcity of studies in emerging-economy contexts, signalling the need for longitudinal and integrative investigations, including tests of industry collaboration as a new dynamic capability. Findings provide university leaders with actionable guidance: implement a student-experience dashboard, adopt a “3E” digital-content strategy (Educate–Engage–Empower), and set clear e-service benchmarks to fortify reputation and sustain competitive advantage.